An Insight into The Knowledge Level of Dairy Farmers About Retention of Placenta in Punjab, India - Devansh; Kasrija, Rajesh; Kumar, Ajeet; Kaur Dhaliwal, Ramandeep; Kumar Sharma, Rakesh (The Indian Journal of Animal Reproduction, 2025)
The present study was conducted on 300 Dairy farmers visiting three main Veterinary institutions (100 farmers from each), namely Teaching Veterinary Clinical Complex (TVCC), Civil Veterinary Hospitals (CVH) and Veterinary Polyclinics of Punjab state to assess the knowledge level of dairy farmers about Retention of Placenta in dairy animals. Data analysis revealed that there are preferences of dairy farmers for mixed farming (cows and buffaloes) as compared to individual cow farming or buffalo farming. Dairy farmers were categorized in to Group I (rearing cows only, n=84), Group II (rearing buffaloes only, n=30) and Group III (rearing both Cow and buffalo, n=186). Most of dairy farmers had medium to large farm size for Group I and Group III farming, while most of dairy farmers in Group II had small to medium farms. There was statistically significant difference between knowledge level of the farmers of Group II and Group III (at P< 0.05) but Group I did not differ statistically significant with Group II and Group III. Majority of the dairy farmers (63.10 %, 60 %, 85.48 % of dairy farmers belonging to Group I, II and III respectively) had medium knowl edge level score. Suitable extension intervention should be done to enhance the knowledge level of dairy farmers about retention of Placenta.